Upaya Meningkatan Kemampuan Menentukan Unsur Unsur Intrinsik Cerita Rakyat Siswa Kelas III SD Negeri 25 Lubuklinggau Melalui Model Pembelajaran Kooperatif Tipe Think Pair And Share (TPS) - Siti Zubaidah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this research is to prove that through cooperative learning model of Think Pair and Share (TPS) type can improve the ability of third grade students of SD Negeri 25 Lubuklinggau in determining the intrinsic elements of folklore. The method used in this research is Classroom Action Research method (PTK) which is preceded by pratindakan data and twice the implementation of the research cycle. Results of test data on pratindakan of 36 students, students who scored 65 or have completed as many as 21 people or 58.33% of the number of students. While students who scored less than 65 or not completed as many as 15 people or 41.67%, with an average grade grade of 61.25. In the first cycle there is an increase in value gains. Students who have completed as many as 26 students or 72.22% while unfinished as many as 10 people or 27.78% with an average score of 66.53. This is an increase of 5.28 or 8.62%. Cycle II also increased, from 36 students who have completed as many as 33 students or 91.67% and unfinished as many as 3 students or 8.33% with an average value of 75.69. If the calculated increase from the pre-action value until the second cycle there is an increase of 16.1%. Thus, the hypothesis that is found in this research is proved, that with the implementation of cooperative learning model Think Pair and Share (TPS) can improve the ability to determine the intrinsic elements in folklore students III SD Negeri 25 Lubuklinggau. Keywords: Cooperative Model, Think Pair and Share, Intrinsic Elements.